Pengaruh Permainan Tradisional Terhadap Keterampilan Motorik Siswa SD Negeri 34 Kubu Kabupaten Kubu Raya - Yanti, Puja Via Dwi (Journal Sport Academy, 2025)
This study aims to determine the effect of traditional games on the motor skills of students at SD Negeri 34 Kubu, Kubu Raya Regency. The study used an experimental method with a One Group Pretest-Posttest design. The sample of the study was 15 third-grade students. The research instruments included a 25-meter back and forth running test, eye-hand coordination, static balance, and dynamic balance. Treatment was given through five traditional games, namely hide and seek, hopscotch, tewor kanal, jump rope, and gobak sodor for 14 meetings. The results showed an increase in motor skills after being given treatment. The average pretest was 14.20 and the posttest increased to 21.93 with a difference in increase of 7.53 points. The Shapiro-Wilk normality test showed a significance value of 0.308 for the pretest and 0.832 for the posttest (p>0.05) so that the data were normally distributed. Furthermore, the results of the Paired Sample t-Test showed a calculated t value of 7.161 greater than the t table of 2.145 with a significance value of 0.000 (p < 0.05). Thus, it can be concluded that traditional games have a significant effect on improving the motor skills of students at SD Negeri 34 Kubu, Kubu Raya Regency.